STRATEGI PENGEMBANGAN KAWASAN GEOSITE KALDERA TOBA PASCA PENETAPAN SEBAGAI UNESCO GLOBAL GEOPARK - Matius Bangun; Dwirosa Junita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
The development of this area will be even more significant with the designation of the Toba Caldera as the Unesco Global Geopark at the meeting of the Unesco member countries on July 4 in Paris. In this research, the formulation of the problem is as follows: a). What are the factors that influence the development of Lake Toba as a tourism area. b) What is the strategy adopted to produce the Toba Caldera as a tourism area regarding local cultural traditions and preserving biodiversity. This research uses the method of literary studies, documentation, field observations plus unstructured interviews with informants. The conclusions of this study are: 1) The strategy of inter-regional cooperation based on the SWOT analysis is in the First Quarter (First), namely using Strength in utilizing Opportunities, 2) In addition to using Strength in exploiting opportunities, it also minimizes weaknesses in overcoming threats. 3), Cooperation between regions is under the coordination of the Lake Toba Tourism Development Authority (BOPDT)., 4 Tourism developed through Attractions, Accessibility, and Ameniyas in empowering local traditions and preserving biodiversity. The recommendations given are for the regencies in the Lake Toba region to make use of regulations to implement cooperation, financial support, cultural potential and regional biodiversity